1)3х^2-28х+9=0
D = b^2 - 4 * a * c = (-28)^2 - 4 * (3) * (9) = 676
x1 = (-b + sqrt(D)) / (2*a)
x2 = (-b - sqrt(D)) / (2*a)
x1 = 9
x2 = 1/3
2)2х^2-8х+11=0
D = b^2 - 4 * a * c = (-8)^2 - 4 * (2) * (11) = -24
___
I*\/ 6
x1 = 2 +
2
___
I*\/ 6
x2 = 2 -
2
3)16х^2-8х+1=0
D = 0, то корень всего один.
x = -b/2a = --8/2/(16)
x = 1/4
4)7х^2-21=0
D = b^2 - 4 * a * c =
(0)^2 - 4 * (7) * (-21) = 588
___
x1 = \/ 3
___
x2 = -\/ 3
если , то .
тогда модуль отрицательного выражения равен противоположному выражению и .
при .
при получим , и тогда .
2)arccos(-корень 2/2)+arcsin0 = П-П/4+0= 3П/4
3)tg(arctg корень 3) =√3
4)sin(4arccos корень 3\2)=sin(4*п/6)=sin(2П/3)=√3/2
5)sin(пи\2 +arccos1)=sin(П/2+0)=1